Encountering local inhabitants' perspectives in terms of authenticity: The example of rural tourism in southern Germany - T. Weidinger (Dos Algarves, 2015)
Effects of globalisation and various standardisation processes in everyday life are currently reflected through individuals’ quests for encountering authenticity. The paper interrogates in which particular ways local inhabitants evaluate rural localities with regard to authenticity by means of local architectural styles and filmic representations. Empirical findings from two qualitative studies carried out in rural Southern Germany are presented. The studies were comprised of qualitative interviews with local inhabitants and representatives in tourism, politics and heritage conservation together with a film analysis of a popular Heimat film shot in the Bavarian forest. Results reveal locals’ critique of modern architectural styles such as “Tuscan houses” as inauthentic, whereby a link between architecture and regional identity (“archidentity”) cannot be established. However, the film analysis brings forth locals’ congruities between filmic representations and their lived spaces. In sum, locals’ perspectives on authentication processes can contribute to re-evaluate localities that are mainly shaped by idealised images for tourism purposes.